Feasibility study of post-harvest handling of betel nut using a self-developed betel nut cutting machine - R Bulan; S Noviasari; M Abrar; K Siregar; M Y Wardhana; R Yana; D Laryea; L Isma; A Sitorus (My University, 2022)
Abstract The betelnut is one of the main products of community agriculture in Aceh province, Indonesia. There are several post-harvest stages to get dried betel nuts ready for sale, including threshing the betel nut from the bunch, cutting the fresh betel nut fruits, drying, and separating the betel nut from the husk. Every post-harvest handling applied to agricultural machinery will generate production costs. Therefore, this article focuses on highlighting the costs generated by post-harvest handling of betelnut (moisture content of 34.68 to 50.54%) in the cutting of the fresh betelnut fruit process using a betelnut cutting machine. The method used in this research is a technoeconomic analysis using a betel nut cutting machine with a capacity of 11.25 to 43.67 kg/hr. The result shows that the fixed cost of operating this machine is 3,276,000 IDR/year and the variable cost for one to three operators is 14,426.5 to 34,426.5 IDR/hr. The economic feasibility study of using this machine is determined by the break-even point parameter, which leads to the use of the machine for the water content of the split betel nut of 50.54% with the number of operators one person will provide the selling price of the betel nut after splitting in the range of 400 IDR/kg. The use of the sale price of the betel nut is split and will provide break-even points in about 1077 hours or about 5.39 months. This indicates that post-harvest handling of the betel nut cutting machine still makes sense, considering that the selling price of dried betel nut at the community level is still much higher than this cost. Furthermore, this study suggests the establishment of a community cooperative to streamline the operating costs of the machinery from the post-harvest handling of betel nuts.
Keywords: Betel; Husk; null